Evaluation of Front Line Demonstration of Pulses in Raebareli District (Indian Journal of Extension Education, 2019)
India is the major pulse producer country. Pulses fix atmospheric nitrogen through symbiotic action. Low productivity of traditional varieties of pulses are a cause of concern for farmer’s at large. To overcome the problem of low yield, Krishi Vigyan Kendra, Raebareli has conducted Front line demonstrations in the different localities of Raebareli district. Cultivation of high yielding varieties of pulses viz. i.e. Blackgram variety Shekhar 1, 60.41 per cent, PU-31, 18.25 per cent, Greengram variety Meha (IPM-9925), 75.60 per cent, Shweta-46.00 per cent, Lentil variety KL-320, 69.70 and 38.84 per cent, KLS-218, 39.21 per cent, Gram variety KWR-108, 63.23 per cent and 71.37 per cent and Field pea variety KPMR- 400, 54.92 per cent more yield of pulse crops as compared to local check. The productivity gain under FLD over farmers practice created awareness and motivated the other farmer’s to adopt scientific crops production and management.